Data sheets for various penicillins: suggested amendments. Issue 15 (20th July 1973) - Unknown
Abstract : Beecham's data sheets for Orbenin (cloxacillin) and Floxapen (flucloxacillin) state that these drugs are 'indicated for the treatment of infections caused by Gram-positive organisms, including infections caused by penicillin-resistant staphylococci'. These drugs are indeed excellent for infections caused by penicillin-resistant staphylococci, but they are less active than benzylpenicillin (penicillin G) or penicillin V against other Gram-positive organisms. 1 The statement would be accurate if it ended '...., especially infections caused by penicillin-resistant staphylococci', but there is a case for listing these latter infections as the only indication. It is also misleading to list among 'typical indications' conditions such as pharyngitis, tonsillitis and otitis externa, which are rarely due to staphylococci and will respond better to another antibiotic if one is needed. In our view the section on uses needs to be rewritten to make these points clear. It should also be stated that cloxacillin is incompletely absorbed from the gut and that its oral use is not advisable in patients with an absorption defect, nor for seriously ill patients (e.g. septicaemia) who need a penicillinase-resistant penicillin. Such patients should be given the drug by injection.